A monitoração eletrônica e a ocorrência de reincidência policial entre os indivíduos do regime semiaberto - Silva, Christianne Corrêa Bento (2023)
Introduction/importance: Since 2018, Manaus has started using electronic monitoring to serve sentences in a semi-open regime, abandoning the traditionally known intramural prison model. During the hearings at the Execution Court for the investigation of disciplinary misconduct, in particular for the commission of a new crime, I observed that some monitored persons were presented as a result of the commission of a new crime, even despite the fact that they were using the electronic ankle bracelet and that they did not feel limited to the point that, the equipment, made them not focus on a new crime, presenting itself as a research problem to describe what is the relationship between serving a sentence in a semi-open regime through the use of electronic monitoring and police recidivism. In this context, the hypothesis arises that there is a relationship between serving a sentence with electronic monitoring and police recidivism. Objective: as a general objective, to analyze the aspects of electronic monitoring in the execution of the sentence in a semi-open regime and the relationship with police recidivism in Manaus, Amazonas and, for that, the following specific objectives are pursued: 1. To describe the aspects of electronic monitoring in the execution of the sentence in a semi-open regime; 2. Discuss the relationship between electronic monitoring and police recidivism in Manaus, from January 2018 to December 2021. Method: to achieve the objectives, a cross-sectional study was used, with a quantitative approach, of the descriptive type . Result: through data analysis, with the elaboration of a technical report and an article, it was evidenced that the rate of police recidivism was 8.09% of those monitored and that it proved to be factors that contribute to the occurrence of the outcome , according to the adjusted analysis, being male, transsexual and declaring having some religion. It is suggested the development of a multimedia application, as one of the ways for monitoring to be used more effectively in the individual's decision to commit a new offense. Conclusion: after descriptive research and bivariate analysis, it was possible to identify the characteristics of individuals serving a sentence in a semi-open regime with electronic monitoring, including those who committed police recidivism. At the same time, through the multiple analysis, it was identified that the occurrence of the outcome is related to the variables age, gender, religion, higher education, housing, area of residence and profession. Finally, the suggested inferences aim to reduce the practice of police recidivism.